Comparison of the Effectiveness of Sexual Education and Sensory, Proprioceptive, and Tactile Exercises on Children's Attachment Styles - Safarnia, Mahdieh; Estaki, Mahnaz; Salehi, Mahdieh (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to compare the effectiveness of sexual education and sensory, proprioceptive, and tactile exercises on children's attachment styles.Methods and Materials: The study employed a quasi-experimental design with pre-test, post-test, and follow-up measurements. Thirty children aged 4 to 7 years were selected from five therapeutic clinics in Tehran using convenience sampling and were randomly assigned to two experimental groups (sexual education and sensory exercises) and a control group. Data were collected using the Randolph Attachment Disorder Questionnaire and the Sensory Integration and Praxis Tests (SIPT). The experimental groups received their respective interventions for five months, while the control group received no intervention. Data were analyzed using two-way repeated measures ANOVA, and Bonferroni post-hoc tests were applied for pairwise comparisons.Findings: The results revealed a significant decrease in attachment disorder scores in the post-test and follow-up phases for both experimental groups compared to the pre-test, while the control group showed no significant changes. The difference between the post-test and follow-up scores was not significant, indicating the stability of the treatment effects over time. Sexual education and sensory, proprioceptive, and tactile exercises were effective in reducing attachment disorders and promoting secure attachment in children.Conclusion: Both sexual education and sensory exercises can be considered effective interventions for enhancing secure attachment in children.